Evaluation of aircraft emissions at London Heathrow Airport. (1st June 2021) - Stacey, Brian; Harrison, Roy M.; Pope, Francis D.
Abstract: A study to monitor Ultrafine Particles (UFP) at Heathrow Airport was undertaken in the autumn of 2017. The campaign followed on from a similar study in 2016, which put UFP at the airport into context with nearby measurements. The objective of the 2017 study was to undertake UFP monitoring at higher time resolution (60 second scans) and in a narrower particle size range (6–100 nm). High resolution data from the NOx, PM and Black Carbon analysers on site was also collected during the survey. Measurements were made at the runway station, LHR2 to attempt to characterise individual aircraft using the runway. Nucleation mode particles are again seen to predominantly originate from the airport, with highest concentrations associated with departing aircraft. While there is some correlation of nucleation particles with NOx and BC, these pollutants, together with PM mass and Aitken mode particles, also show strong associations with winds from off-airport directions. There is some evidence that BC emissions from landing aircraft are enriched in UV-active BC (UVPM), most likely as a result of tyre abrasion upon landing. Comparison of UFP measurements with the 2016 survey was not possible because of the differences in configuration of the SMPS for the two surveys. This observation demonstrates the importance of documenting SMPS configuration, to determine if comparison between published data is possible. Analysis of the 1 minute measurement data with associated aircraft departure information was used to group the data by aircraft type. Larger aircraft departing from the runway recorded higher measurements of nucleation particles and NOx compared to smaller aircraft, while emissions of BC, UVPM and NO2 appear to be dependent upon the age of the engine design, rather than the size of the aircraft. Graphical abstract: Image 1 Highlights: Departing aircraft emit more Nucleation particles then landing aircraft. Larger aircraft emit more UFP than smaller aircraft. Particle size distribution of UFP is very dependent on aircraft activity at the airport. High concentrations of UV-active Black carbon can be seen from tyres during landing. PM10 and PM2.5 concentrations at the airport mostly originate from other sources.